When Non-Muslims Visit Muslims: A Study of Ethnic Chinese Pilgrimage Practices at Ong Tien's Grave in Astana Village, Cirebon (Abrahamic Religions: Jurnal Studi Agama-Agama, 2024)
Cirebon, one of the areas that still preserves traditions from ancient times to the present, upholds pilgrimage as one such tradition. This article highlights a pilgrimage phenomenon whose tradition remains in Cirebon Regency. In Cirebon's pilgrimage tradition, which is quite 'unique,' the Chinese ethnic group carries out a pilgrimage when visiting the grave of Ong Tien in Astana Village, Gunung Jati Subdistrict, Cirebon Regency. According to local beliefs, Ong Tien, a descendant of the Chinese ethnicity, embraced Islam and was one of the wives of Sunan Gunung Jati. In this study, three religious adherents visit Ong Tien's grave: Buddhists and followers of Confucianism. Several questions are outlined: First, what are the beliefs of the Chinese ethnic group when visiting Ong Tien's grave? Second, what are the purposes of the Chinese ethnic group visiting Ong Tien's grave? And third, what activities do the Chinese ethnic group carry out when visiting Ong Tien's grave? I answer these questions using a Social-Anthropological approach. In analyzing the data, I employ a qualitative descriptive analysis method, aiming to explain and analyze the phenomenon of pilgrimage carried out by non-Muslims at Ong Tien's grave
Keywords: Pilgrimage; Tradition; Grave; Ong Tien